2009
DOI: 10.1016/s1875-5372(10)60024-0
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Properties of LaMgAl11O19:Mn2+ and LaMgAl11O19: RE, Mn2+(RE=Eu2+, Gd3+) under UV/VUV Excitation

Abstract: Using H 3 BO 3 as a flux, LaMgAl 11 O 19 :Mn 2+ and LaMgAl 11 O 19 :RE, Mn 2+ (RE=Eu 2+ , Gd 3+) were synthesized by solid state reaction at 1150 for 4 h. ℃ The effect of Mn 2+ on the luminescent properties excited by vacuum ultraviolet (VUV) was investigated. The strong emission spectrum excited by 147 nm is composed of peaks from Eu 2+ and Mn 2+ luminescence in LaMgAl 11 O 19 :(Eu 2+ , Mn 2+) and only Mn 2+ luminescence in LaMgAl 11 O 19 :Mn 2+ and LaMgAl 11 O 19 :(Gd 3+ , Mn 2+). The results show that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Besides, LaMgAl 11 O 19 (LMA) with a magnetoplumbite structure exhibits excellent physical and chemical stability and contains an amount of [AlO 6 ] octahedral sites to accept doped Mn 4+ ions into the LMA lattice [19]. The LaMgAl 11 O 19 host doped with Mn 2+ ions has been reported in a great deal of research [20,21,22,23]. However, the related luminescence property of LaMgAl 11 O 19 /Mn 4+ (LMA/Mn 4+ ) phosphor is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, LaMgAl 11 O 19 (LMA) with a magnetoplumbite structure exhibits excellent physical and chemical stability and contains an amount of [AlO 6 ] octahedral sites to accept doped Mn 4+ ions into the LMA lattice [19]. The LaMgAl 11 O 19 host doped with Mn 2+ ions has been reported in a great deal of research [20,21,22,23]. However, the related luminescence property of LaMgAl 11 O 19 /Mn 4+ (LMA/Mn 4+ ) phosphor is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…J.L. Wang et al [7] studied the effect of mechanical stirring speed on the microstructure and properties of the coatings. It was found that composite coating grains can be refined, when mechanical stirring speed up to 1000 r / min.…”
Section: Parameters Related To the Nanoparticle Dispersionmentioning
confidence: 99%